Elderly adherence to hypertension treatment and nursing interventions - Jênifa Cavalcante dos Santos; Raquel Sampaio Florêncio; Célida Juliana de Oliveira; Thereza Maria Magalhães Moreira (Rev Rene)
Adherence to the treatment of arterial hypertension is a challenge to health professionals. Thus, this study aimed at verifying adherence to treatment of hypertension of elderly patients followed in a group and describe the possible nursing interventions on the clientele. The descriptive research was developed in two phases: between December/2008 and January/2009, we used data collection instrument to assess compliance to treatment; from February to April/2009, we used the technique Focus Group to investigate the nursing interventions and the Collective Subject Discourse to the organization of speeches. 27 elderly people were evaluated and 23 had some degree of noncompliance. We selected 34 nursing interventions to be implemented in patients and ten discourses were consolidated at the end. The study revealed the difficulties of therapeutic regimen, although the clientele owns the knowledge of viable means for implementing nursing interventions.